The Relationship Between Nutritional Status and the Level of Physical Fitness of Sinjai 1 Public High School Students - M. Adam Mappaompo; Akbar Sudirman (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to find out whether there is a relationship between nutritional status and the level of physical fitness of students at SMA Negeri 1 Sinjai. The population of this study were all students of SMA Negeri 1 Sinjai. The research sample consisted of 20 students from SMA Negeri 1 Sinjai. The technique for collecting data on nutritional status is by measuring height and weight, and physical fitness using the Indonesian physical fitness test which consists of 60 m running, sit ups, full ups, vertical jumps and 1200 m running. The research results show that a sig value = 0.001 > 0.05 is obtained, so H0 is rejected and H1 is accepted, meaning that there is a significant joint correlation between nutritional status level and the determination value (R Square) = 0.252 or a joint correlation of 25.2 % While 74.8% was caused by other factors, it can be concluded that there is a relationship between nutritional status and the level of physical fitness of students at SMA Negeri 1 Sinjai.